Drinking Game Participation Among High School and Incoming College Students: A Narrative Review. Issue 1 (January 2016) - Zamboanga, Byron L.; Tomaso, Cara C.; Cloutier, Renee M.; Blumenthal, Heidemarie; Kenney, Shannon R.; Borsari, Brian
Abstract : Abstract: The transition from high school to college has been characterized as a potentially vulnerable period because of decreased parental supervision and increased autonomy. This transition can increase risk for participation in high-risk behaviors such as drinking games (DGs), which are a social drinking activity that encourages intoxication and are associated with negative alcohol-related consequences. To date, there has not been a narrative review of DG research that examines this activity among high schoolers and incoming college students specifically, and thus, the current review bridges this gap. Findings indicate that DG participation is consistently linked to negative consequences (e.g., passing out, becoming sick) and other high-risk behaviors, such as prepartying (drinking before going to a social event). In addition, DG participation is linked to demographic (e.g., age, gender), psychological (e.g., personality, alcohol cognitions), and contextual/cultural factors (e.g., the college drinking culture). These findings have implications for current prevention and intervention efforts and suggest promising directions for future research.